2021
DOI: 10.1109/tcss.2020.3047604
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Community Depression Dynamics Due to COVID-19 Pandemic in Australia

Abstract: The recent Coronavirus Infectious Disease 2019 (COVID-19) pandemic has caused an unprecedented impact across the globe. We have also witnessed millions of people with increased mental health issues, such as depression, stress, worry, fear, disgust, sadness, and anxiety, which have become one of the major public health concerns during this severe health crisis. Depression can cause serious emotional, behavioral, and physical health problems with significant consequences, both personal and social costs included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…60 A multimodal depression model, designed in Australia to detect depression dynamics, showed that individuals became more depressed following the COVID-19 outbreak. 61 Hence, devising a strategy for combating mental health issues during this pandemic should be taken as a prior public health agendum to improve the physical as well as psychological wellbeing of citizens.…”
Section: Discussionmentioning
confidence: 99%
“…60 A multimodal depression model, designed in Australia to detect depression dynamics, showed that individuals became more depressed following the COVID-19 outbreak. 61 Hence, devising a strategy for combating mental health issues during this pandemic should be taken as a prior public health agendum to improve the physical as well as psychological wellbeing of citizens.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted throughout the world have consistently found that the lethal spread of COVID-19 and its associated lockdowns have been associated with greater levels of anxiety and depression at the population level [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Several of these studies also noted greater perceived risk of contracting COVID-19 to be significantly associated with depression [53,56,58,59,62].…”
Section: Depressionmentioning
confidence: 97%
“…Li et al (2020) gather large scale, pandemicrelated twitter data and infers depression based on emotional characteristics and sentiment analysis of tweets. Zhou et al (2020) focus on detecting community level depression in Australia during the pandemic. They use the distant-supervision methodologies of Shen et al (2017) to gather a balanced dataset, they utilise the methodology of Coppersmith et al (2014) to model the rates of depression and observing the relationship with the number of COVID-19 infections in the community.…”
Section: Mental Health Monitoring During Covid-19 Pandemicmentioning
confidence: 99%